ANALYSIS OF RELATIONSHIP MARKETING'S EFFECT ON CUSTOMER LOYALTY AT PT. SUCOFINDO JAMBI - Henny Herawati; Dian Indah Sari; Marhumi Marhumi; I Nyoman Tri Sutaguna (Brilliant International Journal Of Management And Tourism, 2023)
Jambi Province is one of the provinces with the largest number of Palm Oil Mills in Indonesia. The large number of PKS that exist and the number of customers that are not too many make each PKS must be able to maintain its relationship so that sales do not decrease. The existence of intense competition and the need to maintain relationships is the phenomenon behind this research so that the purpose of this research is to analyze the effect of Relationship Marketing Inputs on customer loyalty at PT. Sucofindo Jambi This research was conducted using a questionnaire method on 65 customers of PT. Sucofindo Jambi The data analysis method used is quantitative analysis, namely analyzing through statistical calculations with the help of the SPSS version 19.0 program. The results of data analysis show that understanding customer expectations, building service partnership and total quality management have a positive and significant effect on customer loyalty of PT. Sucofindo Jambi. while the empowering employees variable has no effect and is not significant on customer loyalty of PT. Sucofindo Jambi.